BRONCHIAL OBSTRUCTION SYNDROME IN CHILDREN IN THE CONTEXT OF CLINICAL GUIDELINES AND BRONCHOLYTIC THERAPY - Щербатюк, Наталія; Борис, Зоряна (SWorldJournal, 2024)
Summary. The article provides an analysis of the clinical guideline "Bronchial obstruction syndrome in children" (2020) and practical experience in the treatment of broncho-obstructive syndrome in children with respiratory tract pathology. The aim. To fo